Correlation ofT max volumes with clinical outcome in anterior circulation stroke - Seker, Fatih; Pfaff, Johannes; Potreck, Arne; Mundiyanapurath, Sibu; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (Brain and behavior, 2017)
Background and Purpose: The recent thrombectomy trials have shown that perfusion imaging is helpful in proper patient selection in thromboembolic stroke. In this study, we analyzed the correlation of pretreatment T max volumes in MR and CT perfusion with clinical outcome after thrombectomy. Methods: Forty‐one consecutive patients with middle cerebral artery occlusion (MCA) or carotid T occlusion treated with thrombectomy were included. T max volumes at delays of >4, 6, 8, and 10 s as well as infarct core and mismatch ratio were automatically estimated in preinterventional MRI or CT perfusion using RAPID software. These perfusion parameters were correlated with clinical outcome. Outcome was assessed using modified Rankin scale at 90 days. Results: In patients with successful recanalization of MCA occlusion, T max > 8 and 10 s showed the best linear correlation with clinical outcome (r = 0.75; p = .0139 and r = 0.73; p = .0139), better than infarct core (r = 0.43; p = .2592). In terminal internal carotid artery occlusions, none of the perfusion parameters showed a significant correlation with clinical outcome. Conclusions: T max at delays of >8 and 10 s is a good predictor for clinical outcome in MCA occlusions. In carotid T occlusion, however, T max volumes do not correlate with outcome.
First published: 26 July 2017
Im Titel ist max tief gestellt
Gesehen am 03.07.2018